Mutual energy transfer in a binary colloidal quantum well complex - Yu, Junhong (2020)
Förster resonance energy transfer (FRET) is a fundamental process that is key to optical biosensing, photosynthetic light harvesting, and down-converted light emission. However, in total, conventional FRET in a donor-acceptor pair is essentially unidirectional, which impedes practical application of FRET-based technologies. Here, we propose a mutual FRET scheme that is uniquely bidirectional in a binary colloidal quantum well (CQW) complex enabled by utilizing the d orbital electrons in a dopant-host CQW system. Steady-state emission intensity, time-resolved, and photoluminescence excitation spectroscopies have demonstrated that two distinct CQWs play the role of donor and acceptor simultaneously in this complex consisting of 3 monolayer (ML) copper-doped CQWs and 4 ML undoped CQWs. Band-edge excitons in 3 ML CQWs effectively transfer the excitation to excitons in 4 ML CQWs, whose energy is also harvested backward by the dopants in 3 ML CQWs. This binary CQW complex, which offers a unique mutual energy-transfer mechanism, may unlock revolutionary FRET-based technologies.